Towards an agency-based model of intersex, variations of sex characteristics (VSC) and DSD/dsd health. Issue 4 (23rd November 2020) - Crocetti, Daniela; Monro, Surya; Vecchietti, Valentino; Yeadon-Lee, Tray
Abstract: Agency-based approaches to the health of intersex people and those with DSD focus on bodily autonomy and the cessation of normalising medical interventions until an under-age person can exercise fully informed choice regarding treatment. Discussions regarding intersex agency and health care can be inspired by the social model of health that emerged from disability theory. However, a purely social model is insufficient to address the harms that has been caused by DSD medical interventions, and the healthcare needs that some intersex people have. Drawing on original empirical research conducted in Italy, Switzerland and the UK, this article explores agency-based approaches to intersex and DSD, incorporating the social model's critique of the pathologisation of bodily diversities, whilst supporting the provision of effective healthcare where needed. The article addresses healthcare deficits and their cultural underpinnings. It identifies key impediments to intersex agency, including body normativity and sex and gender binarism. While there has been slight movement towards an agency-based approach to intersex in some national medical settings in the last ten years, there is still a need for change to the conceptualisation of intersex/DSD and subsequent revisions to healthcare provision.